Musculoskeletal disorders in Portuguese welders: effects on bodily pain and health-related quality of life - Lourenco, Lilian (2021)
Background: Musculoskeletal disorders in welders may influence their health-related quality of life. However, few studies have addressed this issue and their results were inconclusive. This study investigates whether there are musculoskeletal disorders with a higher incidence in welders compared to non-welders, and whether these disorders lead to an increase in bodily pain which in turn decreases their health-related quality of life. Methods:A priori analyses of statistical power were conducted to determine the sample size needed to find medium to large statistical effects, for a 0.05 alpha, and critical sampling, combined with snowball sampling, was carried out. The study was cross-sectional, and participants were asked to respond to a survey using validated instruments (N welders = 40, Nnon-welders = 42). Results: As expected, a higher incidence of symptoms of musculoskeletal disorders in the cervical, dorsal, lumbar, and wrists and hands was found in welders in comparison to non-welders. Furthermore, the presence of musculoskeletal disorders, particularly in the lumbar area, was related to an increased bodily pain and decreased health-related quality of life. Conclusion: Welders are exposed to a higher incidence of musculoskeletal disorders that decrease their quality of life. It is essential to increase the awareness of welders, organizations, and regulatory institutions toward this issue in order to motivate the development and implementation of prevention strategies. The need for primary and secondary prevention-type strategies, which have already proven their effectiveness in the context of welding, is highlighted.